2021
DOI: 10.3390/nu13113935
|View full text |Cite
|
Sign up to set email alerts
|

Education Interventions to Improve Knowledge, Beliefs, Intentions and Practices with Respect to Dietary Supplements and Doping Substances: A Narrative Review

Abstract: The misuse of dietary supplements and doping substances is commonly associated with toxicity, nutritional imbalances, and health and psychological consequences. This is alarming especially in light of the increasing prevalence of the use of dietary supplements and doping, particularly among young adults including athletes. There is evidence that education interventions can lead to improved knowledge, intentions, and practices. However, no review has summarized and evaluated the effectiveness of such interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Accurate information is needed to make informed decisions and protect against inadvertent doping and dietary supplement misuse. The integration of nutritional-knowledge programs may be highly valuable to increase the knowledge, beliefs and intentions of athletes who choose to consume dietary supplements [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate information is needed to make informed decisions and protect against inadvertent doping and dietary supplement misuse. The integration of nutritional-knowledge programs may be highly valuable to increase the knowledge, beliefs and intentions of athletes who choose to consume dietary supplements [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that common sources of dietary supplement-related information come from fellow teammates, coaches, the internet, family and friends or their judgment [ 6 ], an educational intervention program is a possible way to improve dietary supplement knowledge among athletes to decrease the risk of dietary supplement misuse and inadvertent doping [ 16 ]. Considering the many risks associated with dietary supplement consumption, a food-first approach is often recommended to all populations when considering the use of dietary supplements.…”
Section: Introductionmentioning
confidence: 99%
“…The widespread use of DS and the numerous contributing factors (such as sources of information, awareness of dietary supplement regulations, perceptions of doping and DS use, contamination of DS, and motivations for DS use) indicate that intervention education programmes designed to focus on improving the knowledge, beliefs, and attitudes towards DS use may be an excellent first line of defence against inadvertent doping. Many reviews focusing on DS use in athletes have found compelling evidence in support of interventional education programmes for athletes (and young athletes, especially), coaches, and parents/family members [ 9 , 11 , 53 , 58 ].…”
Section: Prevention: a Focus On Educationmentioning
confidence: 99%
“…A narrative review focusing on educational interventions to advance understanding, attitudes, behaviours, and practices about DS and doping substances found consensus among the studies, proving educational intervention to be effective at increasing knowledge of DS and doping substances among participants [ 58 ]. The majority of the studies in this review delivered their curricular materials through a variety of methods.…”
Section: Prevention: a Focus On Educationmentioning
confidence: 99%
“…Prevention efforts in school age children and adolescents can be accomplished through behavior change education and teaching them the value of competing within their own physical limitations (Poppel, 2021). It is important to note that many education interventions were successful in changing attitudes and intentions regarding doping (Daher et al, 2021). However, fostering a culture of anti-doping requires prevention and treatment measures in addition to education.…”
Section: The School Nurses’ Rolementioning
confidence: 99%